1991
DOI: 10.1016/0165-2478(91)90144-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of tumor necrosis factor determine the fatal or non-fatal course of endotoxic shock

Abstract: The role of tumor necrosis factor alpha (TNFo0 in endotoxin-induced shock was investigated in pigs receiving 5/~g kg -~ of Escherichia coli endotoxin (LPS)during 60 rain of continuous infusion intothe superior mesenteric artery. I_PS concentration in aortic plasma, as determined by a chromogenic Limtdus amoebocyte lysate (LAL) test, reached a peak of approximately 1000 ng I -t during LPS infusion, and declined rapidly after discontinuation of the infusion. Serum TNF levels were determined by a bioassay using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
3
15
0
1
Order By: Relevance
“…Our study confirms that pigs respond to LPS with a marked increase in the secretion of TNF-· [13,15,51], but we failed to find a difference in circulating TNF-· concentrations between suckling and weaned piglets 1 h after LPS injection. Recently, a positive correlation between high plasma TNF-· levels and lethality caused by endotoxin shock has been reported [52], whereas a low dose of 0.5 Ìg LPS induced sickness behaviour in pigs but failed to increase plasma concentrations of TNF-· [13,14]. The dose of LPS used in our study caused similar increases in TNF-· concentrations in suckling and weaned piglets but revealed a higher intensity of sickness behaviour in weaned piglets.…”
Section: Discussionsupporting
confidence: 67%
“…Our study confirms that pigs respond to LPS with a marked increase in the secretion of TNF-· [13,15,51], but we failed to find a difference in circulating TNF-· concentrations between suckling and weaned piglets 1 h after LPS injection. Recently, a positive correlation between high plasma TNF-· levels and lethality caused by endotoxin shock has been reported [52], whereas a low dose of 0.5 Ìg LPS induced sickness behaviour in pigs but failed to increase plasma concentrations of TNF-· [13,14]. The dose of LPS used in our study caused similar increases in TNF-· concentrations in suckling and weaned piglets but revealed a higher intensity of sickness behaviour in weaned piglets.…”
Section: Discussionsupporting
confidence: 67%
“…Thus the presence of a feverlike state post-heat stress in our model was a novel observation that was observed via our use of biotelemetry. Evidence for the post-heat stress T c elevations as a feverlike state is as follows: 1) severe heat stress induces endotoxemia (4,9,12), 2) circulating pyrogenic cytokines increase during endotoxemia/sepsis (7,25) and heat stress (3,5), 3) the biphasic T c profiles during mouse heat stress recovery (Fig. 2) were similar to those of sepsis and fever induced by endotoxemia or cecal ligation and puncture in mice (17,22), and 4) similar to LPS-induced fever responses (19), the feverlike phase post-heat stress was noted only during the day.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a positive correlation between TNF‐ α levels, severity of shock and fatality (Kenison et al. , 1991; Mozes et al. , 1991; Coyne & Fenwick, 1993; Miyamoto et al.…”
Section: Discussionmentioning
confidence: 99%